Strategic cooperation and consortia building for Indian libraries: models and methods - Maitrayee Ghosh S.C. Biswas V.K.J. Jeevan (Library Review Vol. 55 No. 9, 2006, 2006)
Purpose - The purpose of this paper is to review the state of libraries in India and summarise the strategic cooperative initiatives undertaken to improve user access to electronic information services. Design/methodology/approach - The methodology used included personal interview, e-mail interaction and literature searches. Several Strategies for retrieving information were used across both the professional and research literature [Library Literature, Library and Information Science Abstracts, and Educational Resources Information Center (ERIC)] and the Internet (Google). A variety of search terms were employed to gain a broad overview of the subject and then more targeted terms to examine key aspects of the area of study with greater specificity. The paper also examines a range of general environmental factors impacting on libraries and which must be taken into account to accelerate the pace of beneficial change. It also lists the significant achievements in this field to date. Findings - There are still significant potentials for further implementation of cooperative strategies to enhance networked, electronic information service delivery in India. This paper discusses some of the underlying issues which are presumably delaying the establishment of consortia and which need to be resolved. Research limitations/implications - This area of study is extremely fast moving and regular updating and continuation of this research is required to maintain a grasp of the situation. Practical implications - The negative factors outlined in this paper which militate against the full successful impact of cooperative strategies are clearly set out, in order to help library managers and administrators create practical solutions capable of eliminating these obstacles to progress. Originality/value - This research gives an insight into how consortial strategies can help overcome the resource constraints which characterise library provision in many developing countries, providing a model for other library systems, which face similar problems, to follow